HUBUNGAN PENGETAHUAN IBU TENTANG IMUNISASI HEPATITIS B-0 DENGAN PEMBERIAN IMUNISASI HEPATITIS B-0 DI WILAYAH KERJA PUSKESMAS PADANG ALAI TAHUN 2015 - Ningsih, Mahdalena Prihatin; Rahmawati, Lisa (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Hepatitis B is a silent killer disease. Many people do not know if they have been infected with this disease, so it is too late to be treated. The Higher prevalence of Hepatitis B infection in a certain place makea higher number of children and infants that will be infected by this viruses because of their undeveloped immune body system. A prevention efforts need to be optimized because of the unavailability of Hepatitis B drugs for today. Based on preliminary study conducted at Padang Alai Public Health Care for 10 mothers who have babies, 6 from mothers said they did not know about Hepatitis B-0 immunization in terms of usefulness and delivery time, while 4 others said that they knew about Hepatitis B-0 immunization and their baby had been immunized Hepatitis B-0.The type of this research is analytic description with cross sectional design. The population in this research is all mothers in Padang Alai Public Health Care area with 0-12 month’s babies. The sampling method is a total sampling with 51 people sample. Data collection method is using questionnaires. Data processing is using univariate and bivariate. The results showed that more than half of respondents (62.7%) had low knowledge about hepatitis B-0 immunization, and more than half of respondents (58.8%) did not get hepatitis B-0 immunization.The result of bivariate analysis was found that p value 0.006 (<0,05) so that it can be stated that there is relation of mother knowledge about immunization of hepatitis B-0 with hepatitis B-0 immunization in Padang Alai Public Health Care working area. Keywords: Knowledge, Immunization, Hepatitis B-0